There are indigenous here: reflections about the indigenous protagonism in the comic book from the comic almanac there are scientist here - Champi, Paola; Chohfi, Júlia Melo; Martins, Sarah Marion (9 Arte (São Paulo), 2023)
Based on Analysis of Discourse and relating with the art of scientific communication of comic-books for school public, the discussion about the scientific and popular knowledge are problematized through representativeness and indigenous protagonism. The corpus analyzed consists in the comic book “how many species of fish exists in Amazon basin?” (Quantas espécies de peixes existem na bacia amazônica?). In the comic Almanaque Tem Cientista Aqui! of november, 2022, from rede Conexões Amazônicas.